Marketing Strategies Of Housing Developers To Capture The MM2H Market Segment - Lim, Jing Xin (2012)
Malaysia My Second Home Programme (MM2H) was initiated by the government to allow foreigners who fulfill certain requirements to reside in Malaysia with ten years visa and multiple entries passes. The participants of MM2H programme have increased over the years. It has become a potential market segment for housing developers. This study was done to examine how housing developers to cater this MM2H market segment. In this research, mixed methods were adopted to present a more comprehensive analysis. Data was collected via postal questionnaire survey, face-to-face interview and secondary sources. 41 usable completed questionnaires were returned. Eight interviewed housing developers formed the case studies for this thesis. The questionnaire survey found that only 7.3% of the respondents targeted a single nationality group. One of companies from the case studies targeted only the Koreans and subsequently found that it was a wrong marketing tactic. Also, this study found that most commonly developed product for MM2H house buyers were luxury condominiums and the price range of the dwellings was most frequently set at RM651,000 to RM850,000. Kuala Lumpur was the most preferred location for housing developments to cater for the MM2H segment due to easy accessibility to modern amenities and infrastructure. Lastly, the most executed marketing method by the sampled housing developers was company websites and property fairs in Malaysia. The findings of this study can be used as a reference for housing developers who are interested to tap into the MM2H market segment.